1986
DOI: 10.1159/000183827
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Glycosaminoglycans, Sialic Acid and Lysosomal Enzymes Increase in Nonalbuminuric Diabetic Patients

Abstract: Urinary excretion of glycosaminoglycans (GAGS) and sialic acid (SA), as well as the activity of two renal enzymes related to glycoprotein metabolism, N-acetyl-β-D-glucosaminidase (NAG) and β-galactosidase (GAL), and two others unrelated to glycosaminoglycans and glycoprotein metabolism, γ-glutamyltranspeptidase (γ-Gt) and angiotensin-I-converting enzyme (ACE), were evaluated in 40 insulin-dependent diabetic patients with normal range albuminuria, 21 patients with mesangial glomerulonephritis, and 30 control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…However in our study the increased excretion of NAG in 34% normoalbuminuric diabetic patients was considerably less than some of the other studies. (24). However in all these studies the sample size was small, number of diabetic patients in the range of 15-25 only.…”
Section: Discussionmentioning
confidence: 96%
“…However in our study the increased excretion of NAG in 34% normoalbuminuric diabetic patients was considerably less than some of the other studies. (24). However in all these studies the sample size was small, number of diabetic patients in the range of 15-25 only.…”
Section: Discussionmentioning
confidence: 96%
“…The results of this study indicate that ITF-182, a com pound which is both a NSA1D and an imidazole deriva tive, brings about a reduction in the rate of urinary GAG excretion in 1DD patients in whom an abnormally high urinary excretion of GAGs and other correlated mole cules has been found [3][4][5][6], The meaning of these urinary biochemical abnormalities is still under debate, mainly in view of the contradictory reports on the effects of human and experimental diabetes on systemic proteoglycan me tabolism. In fact, it has been reported both a decreased concentration and biosynthesis of sulfated GAGs, an increase of their degradation, and some molecular changes in proteoglycans.…”
Section: Resultsmentioning
confidence: 68%
“…Diabetes mellitus is characterized among others by both qualitative and quantitative modifications of base ment membrane glycosaminoglycans (G AGs) [ 1,2] which are also mirrored in an altered urinary excretion of G AGs [3][4][5] and other correlated molecules [6], This GAG de rangement seems closely related to some complications of diabetes, namely atherosclerosis and diabetic neph ropathy, for which the most widely accepted viewpoint suggests that the disturbance in glomerular basement membrane GAG metabolism is related to the onset of 'microalbuminuria' [7] which appears to be a good pre dictor of the later development of clinical nephropathy [8], In this setting, any action aimed at correcting GAG metabolism should be able to slow down the onset of diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…This assertion is supported by the serum concentration of the enzyme which is too low to account for the urinary rate of excretion, by the differences of serum and kidney isoenzymes of the enzyme and by the fact that other non-lysosomal kidney enzymes are not increased in diabetic urine (30). In the study by Bomback et al (31) it was found that urinary excretion of Egalactosidase was significantly higher in both diabetic female and male patients compared with controls, whereas the change in the serum level of activity was not statistically significant.…”
Section: Significance Of Lysosomal Enzymuria As a Marker Of The Preclmentioning
confidence: 99%